APOE-ε4 genes may accelerate the activation of the latent form of HSV-1 which would lead to a faster progression of AD - Tang Yanan (BIO Web of Conferences, 2023)
This study investigates the impact of APOE alleles and latent Herpes Simplex Type 1 virus (HSV-1) activation on Alzheimer’s disease (AD) progression using the 5xFAD mouse model. APOE ε4 is recognized as a substantial genetic risk factor for sporadic AD, while HSV-1 has been linked to AD pathogenesis through inflammation and plaque formation. The experimental approach involves the introduction of human neurons carrying latent HSV-1 into 5xFAD mice harboring various APOE alleles (APOE2, APOE3, APOE4), along with stress induction and pharmacological interventions. The study aims to elucidate the combined impact of these variables on AD progression and the formation of Aβ plaques. Our anticipated results suggest that APOE ε4 may accelerate AD development, especially in conjunction with HSV-1 activation, while APOE ε2 may exert a mitigating influence. These findings have the potential to advance our understanding of the intricate mechanisms underpinning AD and provide insights into potential therapeutic approaches. Further exploration of these interactions could offer critical insights into the pursuit of effective AD treatments.